Small bowel volvulus with jejunal diverticulum: Primary or secondary? - Shen, Xiao-Fei (World J Gastroenterol, 2015)
Small bowel volvulus, which is torsion of the small bowel and its mesentery, is a medical emergency, and is categorized as primary or secondary type. Primary type often occurs without any apparent intrinsic anatomical anomalies, while the secondary type is common clinically and could be caused by numerous factors including postoperative adhesions, intestinal diverticulum, and/or tumors. Here, we report a rare case of a 60-year-old man diagnosed with small bowel volvulus using multidetector computed tomography (MDCT) angiography. Further discovery by laparotomy showed one jejunal diverticulum, longer corresponding mesentery with a narrower insertion, and a lack of mesenteric fat. This case report includes several etiological factors of small bowel volvulus, and we discuss the possible cause of small bowel volvulus in this patient. We also highlight the importance of MDCT angiography in the diagnosis of volvulus and share our experience in treating this disease.